Fear and Fertility in Inflammatory Bowel Disease: A Mismatch of Perception and Reality Affects Family Planning Decisions - Mountifield, Réme; Bampton, Peter; Prosser, Ruth; Muller, Kate; Andrews, Jane M. (Inflammatory bowel diseases, 2009)
Smaller family size and voluntary childlessness has been reported in IBD; however, the disease-related reasons for this from a patient viewpoint are not described. The aims were to 1) determine whether IBD patients' perceptions of the issues surrounding IBD, pregnancy, and childbearing influence their reproductive behavior, and 2) describe these specific perceptions and concerns related to fertility and pregnancy.MethodsAll contactable subjects between 18–50 years of age from a hospital-based IBD database were surveyed by postal questionnaire. Data were obtained regarding age, gender, IBD diagnosis and treatment, body image and sexual relationships, as well as both objective and subjective data regarding fertility and pregnancy. Comparisons were made to community norms where data were available. Contingency tables with Fisher's exact test were used.ResultsOf 365 subjects, 255 responded (70%). The mean age was 35.5 years overall, 34.7 years for women. In all, 34% of participants were male, 127 had Crohn's disease (CD), 85 ulcerative colitis (UC), and 5 indeterminate colitis (IC). The average fertility rate was no different between women with CD and UC (1.0 and 1.2 births/woman, respectively; P = 0.553), compared with 1.81 for all Australian women. Although 42.7% of IBD patients reported a fear of infertility, patients only sought medical fertility advice at the same rate as the general population. Fear of infertility was most evident in women, those with CD, and those reporting previous surgery. Specific patient concerns, which appear to have decreased patients' family size, included IBD heritability, the risk of congenital abnormalities, and medication teratogenicity.ConclusionsThe unusually high response rate indicates the centrality of reproductive issues to IBD patients. “Voluntary” childlessness in this group appears to result from concerns about adverse reproductive outcomes that may not be justified. Patients require accurate counseling addressing fertility and pregnancy outcomes in IBD to assist in their decision making.